PENGARUH JENIS TEH TERHADAP KARAKTERISTIK TEH KOMBUCHA - Ita Purnami, Ketut; Anom Jambe, AAGN.; Wisaniyasa, Ni Wayan (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 7 No 2 (2018): Jurnal ITEPA, 2018)
This study aims to know the influence of tea type on the characteristics of kombucha tea and determine the kind of tea that can produce kombucha tea with the best characteristics. This study used Completely Randomized Design (CRD) with the treatment of four types of tea were white tea, green tea, black tea and mixed tea (white tea, green tea and black tea). Each treatment was repeated four times to obtain 16 experimental units. The result of research showed that the best kombucha tea was white tea with characteristics: antioxidant capacity 807.86 ppm GAEAC, total acid 3.58%, pH 4.14, total dissolved solids 10.000Brix, and total sugar 2.08 mg/100g, color (hedonic) rather like, aroma (hedonic) neutral, aroma (scores) kinda typical kombucha tea, taste (hedonic) neutral, taste (scores) tasted kombucha tea, overall acceptance rather like.